The sugar-responsive enteroendocrine neuropeptide F regulates lipid metabolism through glucagon-like and insulin-like hormones in Drosophila melanogaster - Yuto Yoshinari (Nature Portfolio, 2021)
Incretin hormones regulate insulin and glucagon secretion in mammals, but similar peptides have not been characterized in invertebrates. Here the authors show that neuropeptide F functions similar to mammalian incretin in fruit flies, responding to sugar and enhancing insulin-like peptide secretion.